Performance evaluation of PV configurations considering degradation rate and hot spots - Asadi, Suresh Kumar; Sreeranganayakulu, Jinka; Kshatri, Sainadh Singh; Mohammad, Karimulla Syed (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
The rapid emergence and evolution of renewable energy sources such as solar energy has become a vital component of the global effort to meet the energy needs of the future. The major concerns for continuous solar photovoltaic (PV) generation are degradation rate, hot spots. These factors lead to the negative impact on PV mismatch losses, fill factor, maximum power and efficiency. To improve the performance of PV system, the simplest solution is PV panel configuration hence in this paper spider web tie (SWT) based PV Panel configuration in proposed. The proposed configuration is implemented on KC200GT PV Panel of 5×5 size PV panels considering degradation rate, hot spot. The performance of SWT configuration is compared with series-parallel (SP), bridge-link (BL), triple tied (TT), and photovoltaic (PV) panel configurations and performance parameters such as Vmp, Imp, Pmp, Voc, Isc. FF, ∆Pml, and η are calculated in all the cases. In all the cases the proposed SWT configuration exhibited the improved performance.